Control of Investment versus Control of Return in the Regulation of Natural Monopolies - Knight, Bruce W. (Quarterly Journal of Economics, 1930)
Introduction: "fair return on fair valuation" of properties of natural monopolies an economically unsound policy, since it affords unsatisfactory control of investment, 263.—I. Adherence to this policy based upon misinterpretation of monopoly as essentially a phenomenon of distribution, 265.—II. Two approaches to monopoly control, 267.—III. Superiority of "regulated-investment" to "regulated-return" in control of under-invested simple monopoly, 273.—IV. Superiority of "regulated-investment" in control of over-invested simple monopoly, 277.—V. Discrimination as between different services supplied by a given monopoly reducible to same formula as that pertinent to simple monopoly, 282.